Explicație pas cu pas:
C D = B C = 6 cm
D E = F E = 6 cm
a) F P ⊥ D E
[tex]F \: P = \frac{D \: E \sqrt{3}}{2} = \frac{6\sqrt{3}}{2} = 3\sqrt{3} = >F \: P = 3 \sqrt{3} \: cm [/tex]
[tex]D \: P = \frac{D \: E}{2} = \frac{6}{2} = 3 = > D \: P = 3 \: cm[/tex]
[tex]C \: P = C \: D + D \: P = 6 + 3 = 9 = > C \: P = 9 \: cm[/tex]
b) în Δ C F P dreptunghic:
[tex]C \: F^{2} = C \: P^{2} + F \: P^{2} = {9}^{2} + {(3 \sqrt{3})}^{2} = 81 + 27 = 108 = > C \: F = 6 \sqrt{3} \: cm [/tex]
c) C E = C D + D E = 6 + 6 = 12 cm
[tex]C \: E^{2} - C \: F^{2} = {12}^{2} - {(6 \sqrt{3})}^{2} =144 - 108 = 36 = {6}^{2} = F \: E^{2} [/tex]
=> Δ C F E este dreptunghic în F
d) B N ⊥ C F
[tex]C \: F = 2×F \: P => < F \: C \: P = 30°[/tex]
[tex] < B \: C \: F = < B \: C \: D - < F \: C \: P = 90° - 30° = 60°[/tex]
[tex]=> < B \: C \: F = < F \: E \: P = 60°[/tex]
=> Δ B N C = Δ F P E ( cazul I.U.)
[tex]=> B \: N = F \: P = > B \: N = 3 \sqrt{3} cm[/tex]